Atone : religion, conflict, and reconciliation - Lundy, Brandon D., 1976-; Adebayo, A. G. (Akanmu Gafari), 1956-; Hayes, Sherrill (Conflict and security in the developing world., 2018)
This volume engages the unseen impacts of religion-linked conflicts and successful peacebuilding around the world. The authors address the paradoxes of the role of religion in global conflicts to reveal the connections among religion, conflict, and peace.